Physicochemical properties of argessi (Chrozophphora Brochiana) kenaf (Hibiscus Cannabinus) and loofah (Luffa Cylindrica) seed oils - Hussein, Ismail Hassan; Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob (Agricultural Research Corporation (ARC) - Sudan, 2006)
A study on new sources of edible oils namely argessi (Chrozophora brochiana), kenaf (Hibiscus cannabinus) and loofah (Luffa cylindrica) was conducted to quantify the physicochemical characteristics of their seed oil. Percent crude oil content of the three plant species ranges were: 37 - 41, 20 – 23.5 and 19 – 24, respectively. Argessi and kenaf had yellowish and loofah had greenish oil colour. Melting points were: 13.0, 15.0 and 17.5o C; free fatty acid (FFA): 0.82, 1.05 and 4.25%; saponification value (SV): 184.5, 184.8 and 182.4 mg KOH/g; iodine value (IV): 120, 126 and 108 g I/100 g oil; peroxide value (PV): 0.95, 0.98 and 1.20 meq/kg and the unsaponifiable matter: 0.075, 0.052 and 0.09% (w/w), for argessi, kenaf and loofah, respectively. The fatty acid composition (FAC) of argessi oil showed high level of linoleic (C18:2) 44.75%, followed by oleic acid (C18:1) 24.9%, stearic acid (C18:0) 15.6%, palmitic acid (C16:0) 13.9% and some traces of the linolenic (C18:3) 0.50%. FAC for kenaf oil was high in oleic acid (C18:1) 38.78% followed by palmitic (C16:0) 29.07%, linoleic (C18:2) 15.61%, stearic (C18:0) 7.11% and other fatty acids 9.4%. In loofah seed oil, the FAC was 21.15% oleic, 12.01% palmitic, 06.51% stearic, 59.41% linoleic and 0.45% linolenic. The triacylglycerol (TAG) profile of argessi oil showed presence of eleven TAGs: PLO 16.9%, LLL 15.8%, OLL 14.9%, POO 11.7%, OOL 7.7%, PLL 7.5%, SOP 6.0%, SOO 4.0%, POP 3.9%, OOO 2.8% and SOS 2.3%.